Innate seasonal oscillations in the rate of milk secretion in goats - Linzell, J. L. (1973)
1. When goats were kept in continuous milk production for 2-4 yr the rate of milk secretion oscillated in a sinusoidal fashion with a mean wavelength of 49·7 ± 1 weeks, being highest in summer and lowest in winter. 2. Milk [Cl] tended to be higher in summer and [protein] highest in winter but there were no seasonal changes in [fat], [lactose], [Na] or [K]. 3. There were no seasonal oscillations in body weight but the udders were larger in summer than in winter although this did not solely account for the changes in milk yield. 4. Although the autumnal fall in yield and the rise in the spring coincided with the breeding season, seasonal variations also occurred in two ovariectomized animals. 5. Seasonal fluctuations were independent of diet, occurring equally in animals that had never eaten grass but were fed continuously on dry feed and hay ad libitum. 6. Annual oscillations in yield and udder size but not [protein] and [Cl] were also exhibited in two goats kept in a constant temperature chamber at 14 ± 2° C, fed every 2 hr and subjected continuously to 16 hr light and 8 hr dark. These observations have so far persisted for 2 yr in one goat and for 3 yr in the other. However, the wave-length was reduced to 45 ± 1 weeks. Oestrus was suppressed for 2 years.